Histórias de vida de pessoas em situação de rua e os processos de estigmatização pelo uso de drogas - Brito, Rayssa Modesto de Souza (2023)
This research deals with the stigmatization processes of homeless people before the topic ‘drug use’, starting from the following question: How are the processes of stigmatization due to drug use experienced by homeless people? The overall goal of the research is to understand the stigmatization processes caused by drug use on homeless people. As specific goals, we intend on describing the life’s history of homeless people, analyzing the challenges and struggles of life on the streets, and identifying the implications of drug use in the stigmatization processes of homeless people. We used an approach of biographical qualitative research, through the method of life’s history, and we did non-directive interviews and field observations. The place of the research was ‘Centro Pop’ – Downtown Unit. The people who took part in this research were 2 men, a woman, and a person who did not specify their gender; they had been living on the streets for at least 6 months and had been consuming alcohol and/or illegal drugs for at least 1 year. The participants were given fictitious names such as ‘Dimas’, ‘Francisco’, ‘Geni’ and ‘Claudete’. The body of the research comprehends the transcriptions of the interviews recorded in audio, and the data analysis was divided in two steps: First, we described the life’s history of the participants; second, we used Bardin’s thematic content analysis, with the support of the ‘Atlas TI’ software. The analysis’ categories were: ‘living on the streets’; ‘drug use’; and ‘stigmatization processes’. In the description of the life’s history of the participants, we observed that the stigmatization processes due to drug use on homeless people are part of vulnerability paths which precede the home loss, and are influenced by social tags like class, race, gender, and sexuality. The analysis of the ‘living on the streets’ category showed the importance of thinking the stigmatization of homeless people by drug use taking parameters from the street itself, which was presented by the participants as an ambiguous space where the challenges and inventive strategies of resilience and adaptation to the difficulties of life on the streets defy the social rules, such as drug use prohibition. In the ‘drug use’ category, we identified speeches who brought up questions about what is seen as troublesome drug use, since on the streets, drug use-related struggles take on a form of their own. In the ‘stigmatization processes’ category, we identified expressions of prejudice, discrimination, and self loathing, and we discussed how these stigmatization manifestations are portrayals of problems in capitalism’s structure, like poverty, racial and gender inequality. Despite the challenges inherent to a field research in the context of the COVID-19 pandemic, we were able to raise inflection points about the HP and the drugs issue, questioning topics which act as keepers of capitalism’s social order, such as prohibitionism. The research was financially supported by FUNCAP.